SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN ATAS TANAH NEGARA (STUDI KASUS PT X DI KOTA Y) - Maulana, Ayang Fristia (Jurnal Yuridis, 2017)
State land is land directly controlled by the state as stated in Government Regulation No. 24 of 1997 on Land Registration. State land is not an object of Mortgage Rights, the object of mortgage is the right to land with the status of ?Right of Ownership?,? Right to Exploit?, Right to Build? and ?Rights to Use? as described in Article 51 of BAL in Article 4 UUHT. Because state land is not the object of mortgage rights, it is not justified if the state land is guaranteed as the repayment of debtor's debt which is tied up with Power of Attorney Charging the Deposit Rights. In this case, the debtor is a legal entity of a Limited Liability Company engaged in real estate which has located permission for land acquisition. The land to be acquired has the right of ownership status which is then released by the owner with the provision of compensation. After the release of the land rights, the released land will become state land as set forth in Article 19 of the BAL. This is the land which is released as collateral by the debtor to the creditors.